2001
DOI: 10.1084/jem.194.4.529
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Adaptor Containing Src Homology 2 Domain (Bash) Links B Cell Receptor Signaling to the Activation of Hematopoietic Progenitor Kinase 1

Abstract: The B cell adaptor containing src homology 2 domain (BASH; also termed BLNK or SLP-65), is crucial for B cell antigen receptor (BCR)-mediated activation, proliferation, and differentiation of B cells. BCR-mediated tyrosine-phosphorylation of BASH creates binding sites for signaling effectors such as phospholipase Cγ (PLCγ)2 and Vav, while the function of its COOH-terminal src homology 2 domain is unknown. We have now identified hematopoietic progenitor kinase (HPK)1, a STE20-related serine/threonine kinase, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
62
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 52 publications
0
62
0
Order By: Relevance
“…9,10 HPK1 activation involves binding of cell-specific adaptor proteins, relocation to the plasma membrane, autophosphorylation and transphosphorylation by protein kinase D1. [11][12][13] While a role for HPK1 in the regulation of T-cell apoptosis was already suggested, 14 our recent studies have shown proteolytic processing of HPK1 into HPK1-C in non-apoptotic preactivated primary T cells. 15 In this study, the cleavage product HPK1-C sensitizes towards T-cell receptor-mediated cell death, while full-length HPK1 enables activation and survival of T cells.…”
mentioning
confidence: 99%
“…9,10 HPK1 activation involves binding of cell-specific adaptor proteins, relocation to the plasma membrane, autophosphorylation and transphosphorylation by protein kinase D1. [11][12][13] While a role for HPK1 in the regulation of T-cell apoptosis was already suggested, 14 our recent studies have shown proteolytic processing of HPK1 into HPK1-C in non-apoptotic preactivated primary T cells. 15 In this study, the cleavage product HPK1-C sensitizes towards T-cell receptor-mediated cell death, while full-length HPK1 enables activation and survival of T cells.…”
mentioning
confidence: 99%
“…Following recruitment to the TCR, HPK1 is phosphorylated on tyrosine 379 and binds the SH2 domain of SLP-76, which itself is phosphorylated by HPK1 [15][16][17][18][19]. Subsequent transphosphorylation by PKD1 and autophosphorylation within the kinase domain result in full activation of HPK1 [15], which then regulates different cellular responses including apoptosis, activationinduced cell death and autoimmunity [20][21][22].…”
mentioning
confidence: 99%
“…HPK1 is unique in that its expression is restricted to hematopoietic tissues of adults, although it is widely expressed in embryos (4,5). It has been shown that HPK1 is involved in a variety of signaling systems (6), including epidermal growth factor (7,8), transforming growth factor-␤ (9, 10), erythropoietin (11), prostaglandin E 2 (12), and T cell receptor (TCR) and B cell receptor stimulation (13)(14)(15)(16)(17)(18). HPK1 is also involved in Fas ligation-mediated apoptosis (19,20) and NF-B activation (16,21,22).…”
mentioning
confidence: 99%
“…HPK1 is also involved in Fas ligation-mediated apoptosis (19,20) and NF-B activation (16,21,22). During TCR and B cell receptor signaling, HPK1 forms inducible complexes with a number of adaptor proteins, including Nck (15), Crk (15), the linker for activation of T cells (15,18), the B cell adaptor containing Src homology 2 domain (also called BLNK or SLP-65) (16,18), Clnk (17), SLP-76 (18), and Grb2-related adaptor downstream of Shc (also called Grap 2) (13,23,24). HPK1 also constitutively interacts with a variety of adaptor proteins such as Grb2 (7,8,14,15), CrkL (8,15,25), HPK1-interacting protein of 55 kDa (also called SH3P7 and mAbp1) (26,27), and Grap (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation